2019
DOI: 10.2147/ijn.s220380
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cerium oxide NPs mitigate the amyloid formation of α-synuclein and associated cytotoxicity</p>

Abstract: AimAmong therapeutic proposals for amyloid-associated disorders, special attention has been given to the exploitation of nanoparticles (NPs) as promising agents against aggregation.MethodsIn this paper, the inhibitory effect of cerium oxide (CeO2) NPs against α-synuclein (α-syn) amyloid formation was explored by different methods such as Thioflavin T (ThT) and 8-anilinonaphthalene-1-sulfonic acid (ANS) fluorescence spectroscopy, Congo red adsorption assay, circular dichroism (CD) spectroscopy, transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 40 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…Dot blot analysis showed the presence of α-syn in the fractions adsorbed to the CeO 2 NP surface, indicating a direct interaction between CeO 2 NPs and α-syn. These results agree with recently published papers which show how CeO 2 NPs have the best fitting for the active site of α-syn using a computational approach [52,66].…”
Section: Ceo 2 Nps Directly Interact With α-Syn In Vitrosupporting
confidence: 92%
See 3 more Smart Citations
“…Dot blot analysis showed the presence of α-syn in the fractions adsorbed to the CeO 2 NP surface, indicating a direct interaction between CeO 2 NPs and α-syn. These results agree with recently published papers which show how CeO 2 NPs have the best fitting for the active site of α-syn using a computational approach [52,66].…”
Section: Ceo 2 Nps Directly Interact With α-Syn In Vitrosupporting
confidence: 92%
“…Since the N-terminal domain and NAC region are necessary for initiating the α-syn misfolding, small molecules (as CeO 2 NPs) that are capable of stabilizing the physiological α-helical vesicle-bound conformation of α-syn might interfere with its pathogenic aggregation [13,94]. Docking studies [52,66] showed that CeO 2 NPs exhibit excellent interactions with crucial residues of the N-terminal membrane-bound domain of α-syn, and it is possible that the interaction with this domain can prevent the conformational changes leading to misfolding and aggregation of α-syn. Further studies are required to better elucidate this issue, but the present work shows how the use of a simplified model of PD can be informative to assess the anti-aggregation properties of small molecules and better understand how α-syn aggregates can acquire their neurotoxic properties and interact with metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most reports, CeO 2 NPs scavenge reactive oxygen species (ROS), including hydrogen peroxide and free radicals, such as•OH, O 2-,•NO, within the cellular environment, thus attenuating ROS production and organ dysfunction in ROS-related diseases, including myocardial damage, systemic inflammatory reaction syndrome, psoriasis and Alzheimer's disease. [10][11][12][13][14] However, there are also other reports demonstrating that in some acidic environments, such as cancer cells, CeO 2 NPs exhibit oxidase-like activity, enhancing intracellular ROS production and cell toxicity. [15][16][17] In recent years, many researchers have explored the application of CeO 2 NPs in bone regeneration and bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%